Does Reputation Lead to Student Loyalty? The Case of a Private Higher Education Institution, a State University, and a Local College - Lacap, Jean Paolo G.; Cortez, Jaime V. (The South East Asian Journal of Management, 2023)
Research Aims: The current research aims to analyse (1) the direct interrelationships of higher education institutions' (HEIs) reputation, student satisfaction, and student loyalty; (2) the mediating effect of student satisfaction on the relationship between HEI reputation and student loyalty; and (3) the moderating role of HEI type (private HEI [PHEI], state university/college [SUC], local university/college [LUC]) on the links between HEI reputation and student satisfaction, HEI reputation and student loyalty, and student satisfaction and loyalty. Design/Methodology/Approach: All hypothesised relationships were analysed using partial least squares – structural equation modelling (PLS-SEM). Research Findings: The results revealed that (1) HEI reputation has a significant effect on student satisfaction and loyalty; (2) student satisfaction mediates the relationship between HEI reputation and loyalty; (3) a significant difference exists in the effect of reputation on student satisfaction between PHEIs and SUCs; and (4) significant difference exists on the effect of student satisfaction on loyalty between PHEIs and SUCs, and between PHEIs and LUCs. Theoretical Contribution/Originality: The current study lends credence to using the S-O-R model as an appropriate framework in conducting predictive-causal studies that employ the PLS-SEM as the tool for data analysis. Managerial Implication in the South East Asian Context: The current study presents findings which may be used by policymakers and administrators in crafting effective, goal-directed marketing plans for higher education institutions. Research Limitation & Implications: One limitation of this study is the geographic location of its sample. All of the participants were students in the Province of Pampanga, Philippines.